Transfer RNA Misidentification Scrambles Sense Codon Recoding. Issue 15 (2nd September 2013) - Krishnakumar, Radha; Prat, Laure; Aerni, Hans‐Rudolf; Ling, Jiqiang; Merryman, Chuck; Glass, John I.; Rinehart, Jesse; Söll, Dieter
Abstract Sense codon recoding is the basis for genetic code expansion with more than two different noncanonical amino acids. It requires an unused (or rarely used) codon, and an orthogonal tRNA synthetase:tRNA pair with the complementary anticodon. The Mycoplasma capricolum genome contains just six CGG arginine codons, without a dedicated tRNAArg. We wanted to reassign this codon to pyrrolysine by providing M. capricolum with pyrrolysyl‐tRNA synthetase, a synthetic tRNA with a CCG anticodon ( <![CDATA[tRNAPylCCG]]> <inline-graphic xlink:href="ark:/27927/pgg3jxw6gvv" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />), and the genes for pyrrolysine biosynthesis. Here we show that <![CDATA[tRNAPylCCG]]> <inline-graphic xlink:href="ark:/27927/pgg3jxw6h0k" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> is efficiently recognized by the endogenous arginyl‐tRNA synthetase, presumably at the anticodon. Mass spectrometry revealed that in the presence of <![CDATA[tRNAPylCCG]]> <inline-graphic xlink:href="ark:/27927/pgg3jxw6gzh" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />, CGG codons are translated as arginine. This result is not unexpected as most tRNA synthetases use the anticodon as a recognition element. The data suggest that tRNA misidentification by endogenous aminoacyl‐tRNA synthetases needs to be overcome for sense codon recoding.